An Evaluation of the Implementation of Emancipated Learning Program Policy in University of Muhammadiyah Prof. Dr. Hamka - Apoko, Tri Wintolo; Handayani, Isnaini; Hanif, Isa Faqihudin; Hendriana, Benny (Jurnal Paedagogy, 2023)
This study intends to analyze how the students perceive the emancipated learning program’s (MBKM) policies, how lecturers react to the program’s implementation, and how ready the study program is to implement the emancipated learning program (MBKM). This study used a quantitative descriptive method with survey data collection techniques. The instrument used in this study is a questionnaire comprising 19 statements for students, 11 statements for lecturers, and 13 statements for study program leaders. The subject of this study consisted of 98 students, 53 lecturers, and 27 study program leaders. The collected data were then analyzed with data reduction, description, analysis, and conclusion. The results of this study showed that the level of knowledge of students (92%) who participated in the emancipated learning program (MBKM) and lecturers (90%) were good; Students’ interest in participating in the emancipated learning program (MBKM) was also high (98%); emancipated learning program (MBKM) for students and lecturers is very useful (90%); the involvement of lecturers in implementing the emancipated learning program (MBKM) was quite high (68%); the curriculum of the study program that supported emancipated learning program (MBKM) following Permendikbud Number 3 of 2020 was not fully completed (48.1%); and there were still study programs (15%) that do not have an MoU or MoA in implementing the emancipated learning program (MBKM).